INNOVATION PUZZLE banish the innovation killers and become an emerging champion. - Gilsing, Victor, 1969- (ROUTLEDGE, 2025)
Beyond a generic innovation toolkit, this book dissects the hidden biases and behavioral traps that too often doom innovation within companies to failure. It takes the reader on a journey to learn how to banish these innovation killers for good and turn their company into an innovation champion. In The Innovation Puzzle, Professor Victor A. Gilsing reveals that in most cases, these outcomes cannot be blamed on a lack of funding or a failure to follow innovation gurus' playbooks. Often, the real problem is that companies unwittingly build hidden barriers to innovation within themselves. From the systems they use to structure and monitor their business units to their hiring and promotion policies, not to mention their executives' leadership styles. Many of these processes and practices underpinning their core business activities end up depriving innovation of the time, space, vision, talents, and perseverance it needs to succeed. Building on this insight, The Innovation Puzzle helps readers identify and remove these barriers within their own firms. Rather than one-size-fits-all solutions, this volume offers instructive real-world examples. It provides practical, visually rich, and easy-to-apply tools that guide readers toward the measures that will transform their company from a follower into a leader in innovation. Perfect for executives and board members as well as for innovation talents and their managers, The Innovation Puzzle is the key that will unlock the expertise, innovation ambitions, and inspiration your firm needs to realize its true innovation potential and become an innovation champion.
Keywords: Business enterprises -- Technological innovations.; Industrial productivity.; elektronické knihy; electronic books